2011
DOI: 10.4103/0019-5545.91906
|View full text |Cite
|
Sign up to set email alerts
|

Myths, beliefs and perceptions about mental disorders and health-seeking behavior in Delhi, India

Abstract: Objectives:To assess the myths, beliefs and perceptions about mental disorders and health-seeking behavior in general population and medical professionals of India.Materials and Methods:A cross-sectional study was carried out with a sample of 436 subjects (360 subjects from urban and rural communities of Delhi and 76 medical professionals working in different organizations in Delhi). A pre-tested questionnaire consisting items on perceptions, myths, and beliefs about causes, treatment, and health-seeking behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 9 publications
10
109
2
Order By: Relevance
“…This is consistent with other reports, that supernatural belief is associated with unfavorable compliance 26,32 . Those who subscribe to a supernatural cause of mental illness, their decision to continue medication may be influenced by belief, they may have a negative attitude toward medication, and more likely to go with the idea that magicoreligious rituals are helpful 2,3 . Since medical treatment is based on the medical model of illness, which may not go with a patient's model of illness the patient may be less adherent to medication.…”
Section: Level Of Paranormal Beliefmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with other reports, that supernatural belief is associated with unfavorable compliance 26,32 . Those who subscribe to a supernatural cause of mental illness, their decision to continue medication may be influenced by belief, they may have a negative attitude toward medication, and more likely to go with the idea that magicoreligious rituals are helpful 2,3 . Since medical treatment is based on the medical model of illness, which may not go with a patient's model of illness the patient may be less adherent to medication.…”
Section: Level Of Paranormal Beliefmentioning
confidence: 99%
“…In India, it is common in general population and patients with mental illness; and related to evil spirits, witchcraft, astrological influences, bad deeds of previous birth and punishment for a sin 1,2 . Few attempts have been made to explore the paranormal belief in India.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly not useful medications like analgesics and antibiotics were also considered useful by significant proportion of respondents. In a study, only 15.6% of urban and 34.4% of the rural population reported that they would like to go to a psychiatrist when they or their family members are suffering from mental illness [34]. In a study, the professionals gave much high ratings than the public to the helpfulness of antidepressants for depression, and of antipsychotics and admission to a psychiatric ward for schizophrenia.…”
Section: What Can Help Patient With Schizophreniamentioning
confidence: 99%
“…Individuals from both rural and urban residence seek services of faith healers [3]. Utilization of such practices seems to be more common in the lower socio-economic strata, or where access to other forms of treatment is difficult [7,8]. Faith healing practices may be resorted to by those expecting a miracle cure for conditions like cancers, where effective treatment might not be available through the regular treatment modalities [9].…”
Section: Who Goes To Faith Healers and Why?mentioning
confidence: 99%